The Influence of ESG (Environmental, Social, Governance) on Corporate Value in the Indonesian Capital Market - Sinulingga, Tommy Aditia; Nasution, Barran Hamzah; Magda, Marianne (PT. Anagata Sembagi Education, 2025)
In a global era marked by the climate crisis, social pressures, and demands for corporate transparency, the principles of Environmental, Social, and Governance (ESG) have evolved into strategic instruments in the capital market legal system. ESG no longer just reflects ethical preferences, but has become an objective parameter that is juridically recognized by regulators and investors in assessing a company's performance holistically. This study aims to examine the position and normative implications of ESG in the context of Law Number 8 of 1995 concerning the Capital Market, as well as its implementing regulations. The method used is normative juridical, with a legislative, conceptual, and limited comparative approach. The results of the study show that although ESG has not been explicitly regulated in the Capital Market Law, the principles of information disclosure and investor protection provide a basis for legitimacy for the implementation of ESG, which is strengthened by regulations such as POJK No. 51/POJK.03/2017. ESG also reflects the embodiment of the principles of Good Corporate Governance, as well as acting as a non-financial risk mitigation mechanism. Within a dynamic legal framework, ESG serves as an evolutionary form of capital market principles, which combine administrative and substantial compliance. Therefore, strengthening ESG regulations is a normative urgency in building an integrity, competitive, and sustainable Indonesian capital market.